Landscape Ecology - Landscape Ecology (Springer Nature, 2026)
Landscape Ecology, an open access publication, is the flagship journal of a well-established and rapidly developing interdisciplinary science that focuses explicitly on the ecological understanding of spatial heterogeneity.  Landscape Ecology draws together expertise from both biophysical and socioeconomic sciences to explore basic and applied research questions concerning the ecology, conservation, management, design/planning, and sustainability of landscapes as coupled human-environment systems.  Landscape ecology studies are characterized by spatially explicit methods in which spatial attributes and arrangements of landscape elements are directly analyzed and related to ecological processes.
FI 1.12
Q1
Keywords: Life Sciences; Landscape Ecology; Acuerdos transformativos; Transformative agreements; Ecología espacial; Servicios ecosistémicos; Cambio de uso de suelo